2007
DOI: 10.1007/s10663-006-9028-6
|View full text |Cite
|
Sign up to set email alerts
|

The willingness to migrate in the CEECs evidence from the Czech Republic

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…Moreover, housing market variables clearly had a more significant effect on migration than variables proxying labour market conditions. Fidrmuc and Huber (2007) in their study of willingness to migrate in the Czech Republic found that owners of family houses have a significantly lower willingness to migrate than individuals in other types of tenure arrangements. A general observation was that household and personal characteristics are more important than labour market conditions in explaining willingness to migrate.…”
Section: Theoretical Considerations and Empirical Evidencementioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, housing market variables clearly had a more significant effect on migration than variables proxying labour market conditions. Fidrmuc and Huber (2007) in their study of willingness to migrate in the Czech Republic found that owners of family houses have a significantly lower willingness to migrate than individuals in other types of tenure arrangements. A general observation was that household and personal characteristics are more important than labour market conditions in explaining willingness to migrate.…”
Section: Theoretical Considerations and Empirical Evidencementioning
confidence: 97%
“…These are features of many Central and Eastern European (CEE) transition countries. Interregional mobility in CEE transition countries has been explored to some extent by researchers in empirical studies, for example in the case of Russia (Andrienko and Guriev 2003), the Baltic states, mainly Latvia and Estonia (Hazans 2003), Hungary (Cseres-Gergely 2005, Fidrmuc 2004), the Czech Republic (Fidrmuc 2004, Fidrmuc andHuber 2007), Romania (Ghatak and Silaghi 2007), Poland (Fidrmuc 2004, Ghatak et al 2008) and finally a cross-country study by the World Bank (2007). In these studies the main research interest was the relationship between internal migration and labour market conditions usually proxied by unemployment and wage rates, while some of these studies also took into account the effects of housing market conditions (Hegedus 2004, Cseres-Gergely 2005, Andrienko and Guriev 2003, Ghatak et al 2008.This paper aims to consider more explicitly the impact of housing on interregional mobility.…”
Section: Introductionmentioning
confidence: 99%
“…We follow here a broad strand of literature that analyses migration intentions in different countries including, for example, Burda (1993) for Germany, Ahn et al, (1999) for Spain, Epstein and Gang (2006) for Hungary, Fidrmuc and Huber,(2007) for the Czech Republic, Liebig and Sousa-Poza (2004) for 23 countries, Drinkwater, (2003) for Central and Eastern European countries, Krieger (2004) for accession countries, Ester (2007a, 2007b) and Bonin et al (2008) for the EU25. This literature relies on a high correlation between migration intentions and their realisations.…”
Section: Determinants Of Migration Intentions In Eu25 Before and mentioning
confidence: 99%
“…To cite a number of recent studies: Abrams, Hinkle and Tomlins. 1999;Boneva and Frieze 2001;Boneva et al 1998;Burda et al 1998;Drinkwater 2003, Drinkwater andIngram 2008;European Commission 2006;Epstein and Gang 2006;Faini 1999;Fidrmuc and Huber 2007;Frieze et al 2004;Krieger 2004 5. Katz and Stark (1987: 722) present an example that produces a U-shaped pattern by skill level: only the lower level skills and higher level skills migrate.…”
Section: Notesmentioning
confidence: 99%